Bağımsızlıktan sonra Batı Türkistan-Çin ilişkileri - Candemir, Ceylan (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2009)
Bu çalışmada, ?Çin-Batı Türkistan İlişkileri? incelenirken öncelikle Türkistan'ın tanımlanmasına, 1552'de Rusların Kazan'ı işgalinden 1991'de Sovyetler Birliği'nin dağılmasına kadar Batı Türkistan'ın durumuna ve günümüzde bu alanın stratejik önemine yer verilecektir. Türkistan-Çin ilişkilerinin başlangıcı ve tarihi temellerine değinildikten sonra Çin'in Batı Türkistan politikası güvenlik, ortak sınırlar, ticari ilişkiler, enerji, askeri üsler, göç ve terörizm ekseninde incelenecek, ayrıca Çin işgalindeki Türk yurdu Doğu Türkistan'ın bu ilişkilere etkileri açıklanacaktır. Şanghay İşbirliği Teşkilatı çerçevesinde Batı Türkistan Cumhuriyetleri ile Çin Halk Cumhuriyeti ilişkilerinden, son olarak beş cumhuriyetin (Kazakistan, Özbekistan, Türkmenistan, Kırgızistan, Tacikistan) Çin ile askeri, diplomatik ve ekonomik alandaki ikili ilişkilerden bahsedilecektir. Bu değerlendirmede, Batı Türkistan Cumhuriyetleri için Çin'in ekonomik anlamda yeni bir açılım ve jeopolitik açıdan başka ülkelere karşı bir koz olduğu, Çin için ise Türkistan'ın hem sürekli artan enerji ihtiyacı için bir alternatif hem de iç ve dış güvenliği için önemli bir faktör olduğu ortaya çıkmıştır.

In this study, it will be principally given the place of the Turkistan description during the examination of ?the Chinese-West Turkistan relationships?, then the situation of West Turkistan from the Russian invasion of Kazan in 1552 to the Soviet Union?s disintegration in 1991 and the current strategic importance of this region. After the beginning of Turkistan-Chinese relationships and their historical baseline have been referred, the Chinese policy towards West Turkistan, the security, the common frontiers, the commercial relationships, the energy and the military bases will be examined in the scope of immigration and terrorism. In addition to that, it will be explained the influences of the East Turkistan, Turkish residence, being under the Chinese invasion on these relationships. It will be touched on the relationships between West Turkistan Republics and the People?s Republic of China as a part of Shanghai Cooperation Organization and lastly the relationships of the five republics (Kazakhstan, Uzbekistan, Turkmenistan, Kyrghyzstan, Tajikistan) with China in the military, diplomatic and economic fields. In this evaluation, it appears that China is for the West Turkistan Republics a new market expansion in terms of economy and an ammunition towards the other countries from the point of view of geopolitics and Turkistan is for China both an alternative for its continuously increasing need for energy and an important factor for the external and internal security.
Relationships between West Turkistan-China after independence
Keywords: Ekonomi; Economics; Siyasal Bilimler